Rickettsia felis in Ctenocephalides spp. Fleas, Brazil - Riva P. Oliveira (Emerging Infectious Diseases, 2002)
In June 2000, suspected cases of Brazilian spotted fever (BSF) occurred in Coronel Fabriciano Municipality, Minas Gerais State, Brazil. Pooled fleas collected near two fatal cases contained rickettsial DNA. The nucleotide sequence alignment of the 391-bp segment of the 17-kDa protein gene showed that the products were identical to each other and to the R. felis 17-kDa gene, confirming circulation of R. felis in Brazil.